2000
DOI: 10.1095/biolreprod62.6.1495
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chemistry, Nutrient Metabolism, and Organ Weights in Fetal and Newborn Calves Derived from In Vitro-Produced Bovine Embryos1

Abstract: Calves born after in vitro production (IVP) of embryos often show reduced perinatal viability. The present experiment investigated a series of physiological variables in the immediate prenatal and postnatal period of IVP dairy calves. Fetal IVP and control calves (each n = 7) were prepared with vascular catheters at 248+/-1 day gestation (term = 280 days), and blood samples were taken for five days before premature delivery by cesarean section. IVP fetuses compared with controls had significantly elevated arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
4
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
11
40
4
8
Order By: Relevance
“…Values for blood chemistry in animals examined in this study were somewhat similar to those reported by Jacobsen et al (2000) and Sangild et al (2000) for IVP calves, and by Garry et al (1996) and Chavatte-Palmer et al (2002) for clone calves. From this and the results of the aforementioned studies, deviations in blood chemistry appeared to be influenced by calving ease and birth weight.…”
Section: Discussionsupporting
confidence: 88%
“…Values for blood chemistry in animals examined in this study were somewhat similar to those reported by Jacobsen et al (2000) and Sangild et al (2000) for IVP calves, and by Garry et al (1996) and Chavatte-Palmer et al (2002) for clone calves. From this and the results of the aforementioned studies, deviations in blood chemistry appeared to be influenced by calving ease and birth weight.…”
Section: Discussionsupporting
confidence: 88%
“…Under experimental conditions a surgical method (installing catheters in the foetal umbilical vessels) has been used to investigate the differences between IVP and A.I. control foetuses with respect to blood chemistry and hormone levels during the final days before delivery [49]. While IVP foetuses had an elevated haemoglobin (and as a consequence a higher oxygen content) and lower lactate levels compared to arterial samples of A.I.…”
Section: Summarizing Conclusionmentioning
confidence: 99%
“…Besides many (ongoing) studies to unravel the cellular and molecular mechanisms of deviant development of IVF-derived and cloned embryos [11,41,53,64], several authors have reported on placental and foetal growth and pathophysiological events during the perinatal period [18,19,22,26,29,30,47,49,51,59,60]. The bovine foetus and placenta are not easily accessible for (on farm) investigations, especially during the second and third trimester of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that some physiological mechanisms are perturbed as a result of in vitro manipulations apart from changes in imprinting status [44,45]. Studies on fetuses resulting from the transfer of IVP embryos have demonstrated disproportionate organ development in some cases [13,46] but not in others [47,48]. In addition, alterations in the histological development of fetal muscle [49,50] and placental tissue [51,52] have been reported for pregnancies from embryos produced in vitro.…”
Section: Discussionmentioning
confidence: 99%